RETURNING TO THE NATION’S NATIONAL ROOTS – A CONFIDENT STEP FORWARD (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article discusses the importance of preserving national identity, reviving cultural heritage and determining the direction of development of modern society, as well as the fact that a return to national roots is not a step back, but a new use of historical experience, values and spiritual foundations in accordance with the needs of today. The importance of language, history, culture, traditions and worldview of the nation as important factors pointing the way to the future is emphasized. Such a direction will create a basis for confident movement forward, strengthen the unity of society, will contribute to the preservation of national identity and the desire for new achievements in the context of globalization.
Keywords: origin, nation, era of globalization, values, language, material, history.